Platelet Aggregation Is Stimulated by Lactose-lnhibitable Snake Venom Lectins - Ogilvie, Mary L; Byl, JoAnn Wilson; Gartner, T Kent (Thrombosis and Haemostasis, 1989)
Five lactose-specific lectins from snake venoms were tested for the ability to stimulate the aggregation of human platelets. Three of the lectins, bushmaster (Lachesis muta), cottonmouth (Aricistrodon piscivorous leukostoma) and rattlesnake (Crotalus atrox) lectins, consistently stimulated secretion and aggregation. Thrombolectin (Bothrops atrox) occasionally caused aggregation. Copperhead (Agkistrodon contortrix contortrix) lectin did not by itself cause platelet aggregation. Lactose, a specific inhibitor of hemagglutination mediated by these lectins was a potent inhibitor of lectin-induced aggregation. Antiserum specific for bushmaster lectin inhibited aggregation by bushmaster lectin. In contrast, the same antiserum and anti-cottonmouth lectin serum enhanced aggregation by low levels of the other lectins.A variety of substances were assayed in the aggregometer for the ability to inhibit aggregation in response to these lectins. Both secretion and aggregation were inhibited by PGI2 and PGEx. Furthermore, lectin-induced aggregation was completely blocked by trifluoperazine and partially blocked by indomethacin. Monoclonal antibodies specific for GP IIb/IIIa (AP2, A2A9, LJP5, LJCP8) but not monoclonals directed against other platelet membrane proteins (API and AP3) inhibited lectin-induced aggregation. The peptide Arg-Gly-Asp-Ser but not Arg-Ala-Asp-Ser was a potent inhibitor of aggregation.
Keywords: Snake venom; Lactose-inhibitable lectins; Platelets Summary